Synthesis and Photodiode Characterization of Novel Twisted Carbazole Derivatives with 1,3,5-Benzene Core - Gorgun, Kamuran; Caglar, Yasemin; Yakuphanoğlu, Fahrettin (Springer, 2018)
In this study, considering the information given in the literature the Ullman and Suzuki-Miyaura coupling reactions were carried out using carbazole, 1,3,5 tribromo benzene and aryl boronic acid. The synthesized novel carbazole derivative (CPF4) were characterized by 1H NMR and 13C NMR. The photophysical and thermal properties of the synthesized novel carbazole derivatives CPF4 were investigated Graphene oxide (GO) doped CPF4/p-Si photodiodes were fabricated. The electrical properties of these photodiodes were characterized by current-voltage (I-V) and capacitance-voltage (C-V) measurements. The photocurrent properties of the diode were studied under various illumination intensities. The photoresponse properties of the diodes increased with GO content. The results indicate that CPF4: GO/p-Si heterojunctions can be used as a photodetector for optoelectronic applications.
Keywords: Carbazole; Ullman and Suzuki-Miyaura coupling; Graphene oxide; Organic semiconductor; Photodiode